2020
DOI: 10.1111/sed.12698
|View full text |Cite
|
Sign up to set email alerts
|

Systematically variable geometry and architecture of incised‐valley fills controlled by orbital forcing: A conceptual model from the Pennsylvanian Breathitt Group (Kentucky,USA)

Abstract: Incised-valley fills preserved within ancient coastal to shallow-marine successions represent important archives of environmental and sea-level change.Most current knowledge about the origin of incised valleys stems from Quaternary case studies; however, research on pre-Quaternary examples can shed light on valley formation and evolution across longer timespans. This article describes different types of incised-valley fills from Lower to Middle Pennsylvanian fluvio-deltaic successions of the Breathitt Group (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 152 publications
(274 reference statements)
1
2
0
1
Order By: Relevance
“…Basin-wide forcing implies a more significant probability of the occurrence of sandstones within these stratigraphic intervals in the otherwise overall low net-to-gross Westoe and Cleaver Formations. Similar variations in net-to-gross ratios associated with long-eccentricity climate control are suggested for the Upper Carboniferous Upper Silesian (Opluštil et al, 2022) and Appalachian Basins (Le Cotonnec et al, 2020).…”
Section: Low Net-to-gross Targetssupporting
confidence: 63%
See 1 more Smart Citation
“…Basin-wide forcing implies a more significant probability of the occurrence of sandstones within these stratigraphic intervals in the otherwise overall low net-to-gross Westoe and Cleaver Formations. Similar variations in net-to-gross ratios associated with long-eccentricity climate control are suggested for the Upper Carboniferous Upper Silesian (Opluštil et al, 2022) and Appalachian Basins (Le Cotonnec et al, 2020).…”
Section: Low Net-to-gross Targetssupporting
confidence: 63%
“…In the Dutch onshore, van der Belt et al (2015) identified cyclothems paced at a sub-eccentricity periodicity with dominant ∼21 kyr precession and interference of an obliquity component. For the central Appalachian Basin, Le Cotonnec et al (2020) suggested cyclothem forcing by the interference of ∼34 kyr obliquity and ∼100 and ∼400 kyr eccentricity, while for Eastern European Basins a ∼100 kyr short-eccentricity is proposed (e.g. Davydov et al, 2010; Jirásek et al, 2018; Opluštil et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…For example, when evaluating possible fluvial responses to base-level changes (e.g. Yoshida, 2000;Li et al, 2010;Hampson et al, 2013;Le Cotonnec et al, 2020).…”
Section: Discrimination Between Mid-channel and Bank-attached Barsmentioning
confidence: 99%
“…Adicionalmente, el carácter estrato-y granodecreciente de esta asociación de facies es típico de un proceso de relleno de canal fluvial, el cual tiene un significado geológico importante si consideramos que las barras fluviales son una guía aproximada de la profundidad mínima del canal contenedor (Miall, 2006). A partir de esto, se interpreta que los depósitos fluviales en la base de la Formación Olinalá representan un ilustrativo ejemplo de un relleno de valle de incisión fluvial, cuya profundidad fue de al menos 130 m. El reconocimiento de este elemento permite además deducir importantes variaciones en el nivel del mar (Le Cotonnec et al, 2020). De acuerdo con lo anterior inferimos que los depósitos marinos en la parte inferior de la Formación Olinalá fueron erosionados por sistemas fluviales regionales cuando el nivel del mar bajó y dejó expuesta parte de la plataforma (Figura 10a).…”
Section: Modelo De Depósitounclassified